2020
DOI: 10.1136/bmjgast-2020-000373
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of inflammatory bowel disease in patients with eosinophil-predominant colonic inflammation

Abstract: BackgroundInflammatory bowel disease (IBD) is characterised by acute intestinal mucosal inflammation with chronic inflammatory features. Various degrees of mucosal eosinophilia are present along with the typical acute (neutrophil-predominant) inflammation. The effect of intestinal eosinophils on IBD outcomes remains unclear.MethodsThis is a retrospective study. Archived intestinal mucosal biopsy specimens of treatment-naïve IBD patients were examined by two pathologists. The number of eosinophils per high-powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In inflammatory bowel disease, comprising ulcerative colitis and Crohn’s disease, eosinophils have been considered as pro-inflammatory cells associated with increased tissue damage. However, a recent study suggested that inflammatory bowel disease patients with eosinophil-predominant inflammation might have a reduced risk of disease flares and hospitalization [ 52 ].…”
Section: Cellular Mechanism Underlying Eosinophilic Inflammationmentioning
confidence: 99%
“…In inflammatory bowel disease, comprising ulcerative colitis and Crohn’s disease, eosinophils have been considered as pro-inflammatory cells associated with increased tissue damage. However, a recent study suggested that inflammatory bowel disease patients with eosinophil-predominant inflammation might have a reduced risk of disease flares and hospitalization [ 52 ].…”
Section: Cellular Mechanism Underlying Eosinophilic Inflammationmentioning
confidence: 99%
“…Apart from monocyte-derived macrophages, other polymorphonuclear cells such as neutrophils and eosinophils are recruited into the inflamed mucosa in IBD [ 165 , 166 ], but their role in promoting IBD-associated cancer has not yet been well addressed. Interestingly, expression of the transcription factor BATF3 in intestinal epithelial cells promoted the transcription of CXCL5, which together with CXC chemokine receptor (CXCR)- 2 stimulate neutrophil recruitment, which was associated with increased CAC development in AOM/DSS-treated mice [ 167 ].…”
Section: The Role Of the Immune System In Ibd-associated Cancermentioning
confidence: 99%
“…However, there are conflicting results regarding the association of eosinophil numbers and disease severity in humans. This is revealed by a recent study reporting that patients with eosinophil-predominant inflammation have a lower risk of disease flares and hospitalization than those with a neutrophil-predominant inflammation [ 87 ]. It is worth noting that an increased number of eosinophils is a hallmark not only of IBD but also of a different disease, known as eosinophilic colitis (EC) [ 88 ].…”
Section: Type 2 Associated Immune Cells In Ibdmentioning
confidence: 99%